From Traditional to Digital: Barriers and Opportunities for Small Traders in the Post-Pandemic - Mu’arofah, Afrila; Fuad, A. Zaky (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study examines the digital transformation of Warujayeng Market, a traditional rural market in Indonesia, focusing on the barriers and opportunities faced by small traders during post-pandemic recovery. While existing literature predominantly analyzes urban and formal sector digitalization, this research addresses critical gaps by investigating how socio-cultural factors shape technology adoption in informal rural markets. Employing a mixed-methods approach combining longitudinal surveys (n=127), ethnographic observations, and platform analytics, the study reveals three key findings: (1) digital adoption follows nonlinear, kinship-mediated pathways rather than conventional diffusion patterns; (2) traders develop innovative hybrid practices (